Model of psychopathogenesis of mental disorders in patients with pneumoconiosis - V. V. Chuhunov; L. A. Vasyakina (Zaporožskij Medicinskij Žurnal)
The study solved an important scientific problem of description, systematization and analysis of mental disorders of pneumoconiosis. On the basis of clinical-psychopathological, psychodiagnostic and anamnestic investigation mechanisms of syndromogenesis, syndromokinesis, syndromotaxis of psychiatric disorders in patients with pneumoconiosis are defined and the model of psychopathogenesis of mental disorders in this group of patients is developed. Main groups of psychological reactions in patients with pneumoconiosis are singled out, three basic modes of behavior and four clinical types of comorbid mental disorders of pneumoconiosis in measures of revealed psychopathogenesis are defined.